Hot seat strategy to improve spike accuracy, confidence and motivation in volleyball learning - Alaa Naji, Saif (Citius : Jurnal Pendidikan Jasmani, Olahraga, dan Kesehatan, 2025)
This study aims to analyze the effect of using the "Hot Seat" teaching strategy in improving the accuracy of high school students in volleyball spiking skills. This study also highlights how the strategy plays a role in improving students' self-confidence and motivation, in line with the increasing attention to the importance of active learning engagement in physical education. The main objectives of this study were to assess the effectiveness of the "Hot Seat" strategy in improving the accuracy of volleyball spiking performance and building students' self-confidence and evaluate its effect on motivation to achieve. The research method used an experimental design. The study sample consisted of 40 students who were randomly divided into two groups, and the data were analyzed using SPSS software to compare the results between groups. The results showed that the experimental group experienced significant improvements in all measured variables, including spike accuracy, self-confidence, and achievement motivation, when compared to the control group. The interactive "Hot Seat" strategy was shown to encourage critical thinking and active learning, resulting in deeper understanding and significant improvements in skill performance. Conclusion, the "Hot Seat" approach is an effective strategy in improving technical performance as well as psychological attributes of students in the process of learning sports education, and is able to transform students from passive recipients of information into active learners.